IMPROVING ENGLISH SPEAKING SKILL THROUGH "ROLE-PLAY"TECHNIQUE - ikhwan muslim (Journal of English Language and Literature (JELL), 2017)
The Purpose of this study is to get the empirical knowledge of the Role-play technique to improve speaking ability, to know if the role-play effective in teaching speaking, to find the answer if the role is effective to improve English speaking ability. The technique of the research is qualitative. The data from field was done through observation in the classroom. Here the writer directly taught the students and observed students’ activities in speaking class. The writer explains the finding and gives some samples of role-play technique, activities in teaching and how to teach speaking through role-play technique